2008
DOI: 10.1111/j.1468-3083.2007.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character profile of patients with psoriasis

Abstract: The current study shows that psoriasis patients have distinctive temperament and character dimensions when compared with the control group. We suggest that evaluation and treatment of psoriasis should also include psychosomatic approaches in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 29 publications
3
16
0
1
Order By: Relevance
“…KIlIç et al . [ 21 ] have investigated 105 patients with psoriasis and found that the patients had significantly higher scores of harm avoidance and lower scores of being self-directedness than the control group. Reward dependence, persistence, fear of uncertainty, harm avoidance, self-directedness, cooperativeness and self-transcendence scores were found to be significantly higher in hyperhidrosis patients when compared with healthy controls [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…KIlIç et al . [ 21 ] have investigated 105 patients with psoriasis and found that the patients had significantly higher scores of harm avoidance and lower scores of being self-directedness than the control group. Reward dependence, persistence, fear of uncertainty, harm avoidance, self-directedness, cooperativeness and self-transcendence scores were found to be significantly higher in hyperhidrosis patients when compared with healthy controls [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower scores in Purposefulness (SD2), Resourcefulness (SD3), and total Self Directedness (SD) scores indicated that PFH patients might have difficulty to define, set, and pursue meaningful goals [8,10]. Low self-directedness scores of PFH cases seem compatible with results of other similar psychosomatic diseases [15-17]. It is inevitable that these individual’s success to tolerate stress and to cope with stress is low.…”
Section: Discussionmentioning
confidence: 99%
“…Kılıç et al found higher Harm Avoidance scores and lower Self-directedness scores in patients with psoriasis than healthy controls [15]. In contrast, Güler et al found that temperament properties of psoriasis, vitiligo, and neurodermatitis cases did not differ from each other and their character scores were similar to the healthy controls [19].…”
Section: Discussionmentioning
confidence: 99%
“…2006;Hakala ve ark. 2006) ve migren ya da irritabl barsak sendromu gibi diğer psikosomatik durumlar için de araştırmalarda gösterilmiştir (Kılıç ve ark. 2008;Sanchez-Roman ve ark.…”
Section: Introductionunclassified